2007
DOI: 10.1111/j.1399-6576.2007.01463.x
|View full text |Cite
|
Sign up to set email alerts
|

Choice reaction time in patients with post‐operative cognitive dysfunction*

Abstract: Post-operative cognitive dysfunction is associated with impaired performance in the CRT test but the test is a poor predictor of POCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…However, all tests have their limitations, and there is no consensus concerning which test should be routinely used in the assessment of POCD [14]. Some tests are not specific enough or have a wide variation and are, therefore, not well suited to detect subtle changes in the cognitive performance of a patient [35]. To eliminate this problem, multiple tests are used to assess different domains of cognitive function, such as orientation, memory, executive functions, concentration, and mathematical functions.…”
Section: Incidence and Diagnosismentioning
confidence: 97%
“…However, all tests have their limitations, and there is no consensus concerning which test should be routinely used in the assessment of POCD [14]. Some tests are not specific enough or have a wide variation and are, therefore, not well suited to detect subtle changes in the cognitive performance of a patient [35]. To eliminate this problem, multiple tests are used to assess different domains of cognitive function, such as orientation, memory, executive functions, concentration, and mathematical functions.…”
Section: Incidence and Diagnosismentioning
confidence: 97%
“…It is known that difference between simple and choice RT implies cognitive dysfunction. [5,6] Investigators have shown cognition is delayed in metabolic syndrome. Although delayed choice RTs indicate involvement of cognition, they cannot quantify how much time is required for cognition.…”
Section: Introductionmentioning
confidence: 98%
“…It is known that a difference between simple and choice RT implies cognitive dysfunction. [1112] Investigators have shown that choice RTs are delayed in hypertension. Although delayed RTs indicate involvement of central processing, they cannot quantify how much time is required for central processing.…”
Section: Introductionmentioning
confidence: 99%